Effectiveness of stress management program on occupational stress and coping strategies among public health nurses in Amman, Jordan - Alkhawaldeh, Ja'far Mohammad Aqeel (2020)
Occupational stress (OS) has been recognized as one of the most common health problems among nurses worldwide. In particular, about 74% of nurses experience severe occupational stress. Nursing professionals are constantly placed at the forefront in the area of healthcare due to which they are readily exposed to the threat of professional stress. Over the years, more nurses have experienced high level of occupational stress in the workplace, which can lead to many mental and physical disorders. This study aimed to develop, implement and evaluate the effectiveness of stress management interventional program (SMIP) in reducing occupational stress and improving coping strategies (CS) among public health nurses (PHNs). A cluster-randomized controlled trial was carried out in eight comprehensive health care centers (CHCCs); four centers were randomly assigned to each experimental and control group. One hundred and seventy nurses were selected randomly, and data were collected by using the Nursing Stress Scale (NSS) & the Brief Coping Orientations to Problems Experienced Scale (COPE) over three data collection times. Both descriptive and inferential statistics (Repeated measure ANOVA, Independent t-test, Multiple Regression, Chi-square) were used to answer the research questions of this study. The study results showed that both the levels of occupational stress and coping strategies were significantly different between the two study groups over the three data collection points (P>0.05). Also, this study indicated the sex of the nurses was slightly correlated with their perceived occupational stress, female nurses perceived slightly lower occupational stress than males on average. Additionally, the study revealed that nurses’ age is the most common predictors of work-related stress for Jordanian nurses. In addition, the findings showed that ‘Workload’ was the strongest stressor perceived by Jordanian PHNs followed by the factor ‘Conflict with Physicians. Based on the findings of this study, the stress management interventional program is an effective noninvasive method that can be used to reduce occupational stress levels and improve coping strategies for public health nurses. Therefore, the implementation of stress management interventions in healthcare is likely to help nurses manage occupational stress in practice.